A4NH CGIAR partner consultations BD ETH - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Outcome of meetings translated into a food system narrative brief, highlighted on A4NH website, introduced at System Council meeting, and in CRP meetings of FTA, FISH, in meeting with French partners, and presented at different international meetings/conferences.